Algebra 2: Answer Key An Incremental Approach - Saxon, John H., Jr (Norman, OK : Saxon Publishers, Inc., 2003)
This Saxon Algebra 2 Home Study Kit includes the Student Textbook, Test Book/Answer Key Packet, and Solutions Manual. Traditional second-year algebra topics, as well as a full semester of informal geometry, are included with both real-world, abstract and interdisciplinary applications. 129 lessons cover topics such as geometric functions, angles, perimeters, and proportional segments; negative exponents; quadratic equations; metric conversions; logarithms; and advanced factoring.
Grade 10
Grade 11
Keywords: Mathematics -- Algebra